Pollution status evaluation of some heavy metals along some surface water sources by multivariate data analysis at Sulaimani governorate - Majid, Salih N.; Khwakaram, Ahmed I.; Gado, Chalang S. H.; K.Majeed, Bzhwen (Sulaimani Journal for Pure and Applied Sciences, 2018)
In Sulaimani Governorate, Kurdistan Region, Iraq (KRI), the total concentration of eleven (11) transitional heavy metals were examined by inductively coupled plasma-atomic emission spectroscopy (ICP-AES) technique in water samples at 8 sites ( S1 to S8) along Qalyasan Stream and Tanjaro River; also S9 was included in Darbandikhan Lake, S9 is a site located after the confluence of polluted Tanjaro River with Darbandikhan Lake water bodies by about 9 km. Water samples were taken on five dates (D1, D2, D3, D4, and D5) from March 2015 till July 2015 at each site of the total nine (9) selected sites along the water sources. Because those water sources are used as a direct sink for the untreated domestic and industrial wastewater effluents and they are in the meanwhile used as a main sources for multi human uses such as; drinking, irrigation purpose and industrial activities. Therefore, the objectives of this study were; evaluation the pollution status of the 11 transitional heavy metals by multivariate data analysis, the study also aimed to define the most polluted sites along the water sources during the studied period. In the present study the results showed that the overall mean concentrations of the studied transitional metals illustrated the following abundance decreasing trend; Fe (6874.30) ˃ Mn (378.98) ˃ Cr (114.44) ˃ Ni (77.63) ˃ Zn (66.71) ˃ V (21.10) ˃ Cu (19.47) µg L-1. Moreover, the concentrations were generally exceeded the criteria of WHO drinking water quality in some observations for those metals that have a defined guideline values by WHO. Additionally, S4 and S5 in D5 of sampling date had particularly the maximum levels for the upper and lower limit concentrations of the studied transitional metals. Consequently, S4 and S5 could be regarded as hot-spot sites or contaminated sites. PCA results indicated a total variance of 82.34 % and 11.61 % among the studied transitional metals and sites respectively. On the other hand, the dendrogram plot classified the nine sites of the studied surface water into three major groups at a significant dissimilarity percent of about 48%. Furthermore, S1 and S9 revealed the highest similarity, in contrast to that, S1 showed the highest dissimilarity with S5.
Keywords: Surfaces water sources; Transitional heavy metals; Wastewater; principal component analysis PCA; Agglomerative Hierarchical Clustering AHC